1998
DOI: 10.1007/s000110050336
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of selectin L and integrin CD11b/CD18 (Mac-1) induces release of gelatinase B (MMP-9) from human neutrophils

Abstract: Ligation of selectin L and integrin CD11b/ CD18 provides stimulatory signals to neutrophils which induce secretion of gelatinase B that may facilitate their transmigration into sites of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…These data suggest that this Thy-1-mediated MMP-9 stimulation is exclusively mediated by the interaction of Thy-1 with the b2-integrins on neutrophils. Our data are in accordance with studies showing that cross-linking of Mac-1 on neutrophils with antibodies induced the release of MMP-9 [29]. Additionally, interaction of another b2-integrin, LFA-1, with ICAM-1 on T-lymphoma cells also has been shown to stimulate MMP-9 secretion [30].…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that this Thy-1-mediated MMP-9 stimulation is exclusively mediated by the interaction of Thy-1 with the b2-integrins on neutrophils. Our data are in accordance with studies showing that cross-linking of Mac-1 on neutrophils with antibodies induced the release of MMP-9 [29]. Additionally, interaction of another b2-integrin, LFA-1, with ICAM-1 on T-lymphoma cells also has been shown to stimulate MMP-9 secretion [30].…”
Section: Discussionsupporting
confidence: 92%
“…However, MMP-1 and MMP-9, two of the IL-1-and tumor necrosis factor ␣-inducible MMPs investigated in this study (31), are also known to be secreted by inflammatory cells like neutrophil granulocytes (MMP-9) and monocyte/macrophages (MMP-1 and MMP-9) (32). Ligation of adhesive receptors (Lselectin and integrin CD11b/CD18 [Mac-1]) has been shown to induce the release of MMP-9 from human neutrophils, where it is stored in specific granules (33). Also, differential production of MMP-9 by the synovial membrane has been recently reported (34).…”
Section: Discussionmentioning
confidence: 99%
“…It was initially observed that antibodies blocking α 5 β 1 integrin-mediated adhesion induced MMP expression in fibroblasts (Werb et al, 1989). Later studies revealed that integrin-mediated signals are general regulators of MMP expression, as α 2 β 1 integrin regulates MMP-1 expression (Riikonen et al, 1995;Dumin et al, 2001), antibodies to α 3 β 1 integrin-tetraspanin complexes induce MMP-2 expression (Sugiura and Berditchevski, 1999), and α M β 2 and α 3 β 1 integrin ligation stimulates MMP-9 expression (Wize et al, 1998;Larjava et al, 1993). The effects on MMP expression are very specific.…”
Section: Expression and Secretion Of Gelatinases And Other Mmpsmentioning
confidence: 99%